1992
DOI: 10.1007/bf02260906
|View full text |Cite
|
Sign up to set email alerts
|

Brain gamma-aminobutyrate aminotransferase (GABA-T) and monoamine oxidase (MAO) in patients with Alzheimer's disease

Abstract: Activities of Gamma-aminobutyrate aminotransferase (GABA-T) and Monoamine oxidase (MAO)-A and -B were estimated in postmortem brains from 6 control subjects without psychiatric or neurologic disorders and 8 histopathologically verified cases of patients with Alzheimer's disease and senile dementia of Alzheimer type (AD/SDAT). The enzyme activities were examined in four cortical brain regions, three nuclei in the basal ganglia, thalamus and white matter. GABA-T activities in the cortical regions (frontal, parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 57 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…The MAO-B increase could be due to the local infiltration of glial cells in these areas as MAO-B is mainly expressed in this cell type, a significant proportion of which are found in the proximity of -amyloid plaques (a hallmark of AD pathology) [32,88,94]. MAO-A activity and MAO-A mRNA are also reported to be elevated in several areas of the AD brain including the occipital cortex, frontal lobe of neocortex, parietal cortex, and locus coeruleus [93,95,96] as well as in the caudate nucleus, thalamus and white matter [97]. Although there are also reports of decreases in MAO-A activity in AD brains [95,98], it is important to realize that a substantial amount of MAO-A (i.e.…”
Section: Recent Observations Reveal An Effect Of Mao-a That Is Indepementioning
confidence: 98%
“…The MAO-B increase could be due to the local infiltration of glial cells in these areas as MAO-B is mainly expressed in this cell type, a significant proportion of which are found in the proximity of -amyloid plaques (a hallmark of AD pathology) [32,88,94]. MAO-A activity and MAO-A mRNA are also reported to be elevated in several areas of the AD brain including the occipital cortex, frontal lobe of neocortex, parietal cortex, and locus coeruleus [93,95,96] as well as in the caudate nucleus, thalamus and white matter [97]. Although there are also reports of decreases in MAO-A activity in AD brains [95,98], it is important to realize that a substantial amount of MAO-A (i.e.…”
Section: Recent Observations Reveal An Effect Of Mao-a That Is Indepementioning
confidence: 98%
“…Studies have shown that activated MAO in the brains of patients with AD is a biomarker for AD (35)(36)(37). This was demonstrated by [ 11 C]-L-deprenyl using whole hemisphere autoradiography (38)(39)(40), epidemiology (41,42), morphology (43), as well as single-photon emission computed tomography (44).…”
Section: Involvement Of Mao In Neurodegenerationmentioning
confidence: 99%
“…With age, the concentration of MAO-B in the brain increases (Oreland & Gottfries, 1986). A number of studies in patients with AD have shown that up-regulated MAO is a reasonable biomarker for the disease (Sparks, Woeltz, & Markesbery, 1991;Oreland & Gottfries, 1986;Sherif, Gottfries, Alafuzoff, & Oreland, 1992) with levels significantly up-regulated to as much as 30% (Zellner et al, 2012). Such elevated and up-regulated levels of MAO may contribute to the oxidative stress and cognitive impairment through neuroinflammation as MAO generates hydrogenperoxide and ammonia which are among the main culprits contributing to the formation of amyloid plaques (Huang et al, 2012;Zheng, Fridkin, & Youdim, 2012).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%